2015
DOI: 10.1002/jgm.2825
|View full text |Cite
|
Sign up to set email alerts
|

The dependence of efficiency of transmembrane molecular transfer using electroporation on medium viscosity

Abstract: These findings demonstrate that transfection is very susceptible to medium viscosity and highlights the importance of the electrophoretic component in experiments when a considerable transfection level is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…A recent study shows that, after using Ficoll to increase medium viscosity and so reduce DNA mobility and electrotransfer, the application of an LV pulse in addition to the HV one can recover to some extend the transfection efficiency. This reinforces the hypothesis of DNA electrophoresis being crucial for DNA electrotransfer [188]. This observation was confirmed both in vitro and in vivo for numerous tissues [29, 138, 189-195].…”
Section: Gene Electrotransfersupporting
confidence: 86%
“…A recent study shows that, after using Ficoll to increase medium viscosity and so reduce DNA mobility and electrotransfer, the application of an LV pulse in addition to the HV one can recover to some extend the transfection efficiency. This reinforces the hypothesis of DNA electrophoresis being crucial for DNA electrotransfer [188]. This observation was confirmed both in vitro and in vivo for numerous tissues [29, 138, 189-195].…”
Section: Gene Electrotransfersupporting
confidence: 86%
“…The previous research on electroporation optimization focused mostly on the empirical determination of input parameters that describe electric field or single characteristics of the medium [31]. However, the relationship between the input parameters and the therapeutic outcome is indirect, as the final state of the system is achieved over time due to the redistribution of the constituents induced by biophysical processes.…”
Section: Discussionmentioning
confidence: 99%
“…In the specific case of PI, it has been suggested that extracellular conductivity might have an influence not only of permeabilisation but also on the electrophoretic transport of propidium since it can be enhanced at low conductivity 32 . In the case of bleomycin, no influence of the conductivity on the transport is expected since transport occurs almost exclusively by diffusion and is not transported by electrophoresis 33 . However, a thorough study using different markers would re-inforce the present data and enable to draw larger conclusion regarding the impact of extracellular conductivity on permeabilisation.…”
Section: Discussionmentioning
confidence: 99%